2016
DOI: 10.1590/1678-4685-gmb-2014-0343
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset breast cancer patients in the South and Southeast of Brazil should be tested for the TP53 p.R337H mutation

Abstract: Germline TP53 mutations are associated with Li-Fraumeni syndrome (LFS), a disease that predisposes carriers to a wide variety of early onset tumors. In southern and southeastern Brazil, a high frequency of a germline TP53 mutation, p.R337H, was diagnosed in 0,3% of the population due to a founder effect. Carriers are at risk for developing cancer but the penetrance is lower than in typical DNA binding domain mutations. To date, only a few families were detected and diagnosis of carriers remains a challenge. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
(17 reference statements)
1
17
0
2
Order By: Relevance
“…Individuals with this mutation have a similar lifetime cancer prevalence to other LFS carriers (about 90%) but a lower penetrance at young ages (< 20% at age 30 years, compared to 50% in other LFS carriers) [ 19 ]. It has been suggested that women affected with breast cancer under the age of 45 years in Southeast and Southern Brazil should be offered testing for this mutation, irrespective of family history [ 20 ]. The R337H mutation is not common among women diagnosed with breast cancer in Portugal [ 21 ].…”
Section: Founder Mutationsmentioning
confidence: 99%
“…Individuals with this mutation have a similar lifetime cancer prevalence to other LFS carriers (about 90%) but a lower penetrance at young ages (< 20% at age 30 years, compared to 50% in other LFS carriers) [ 19 ]. It has been suggested that women affected with breast cancer under the age of 45 years in Southeast and Southern Brazil should be offered testing for this mutation, irrespective of family history [ 20 ]. The R337H mutation is not common among women diagnosed with breast cancer in Portugal [ 21 ].…”
Section: Founder Mutationsmentioning
confidence: 99%
“…The most notable property of p53 is its action as a transcription factor [83]. We found three articles that studied variations in TP53, all in Brazilian populations [31,84,85]. These articles studied the c.1010G>A (p.R337H) mutation, which occurs at a high frequency in southern and southeastern Brazil [86][87][88][89][90].…”
Section: Other Bc Susceptibility Mutations In Central and South Amerimentioning
confidence: 99%
“…Giacomazzi et al [84] reported that the prevalence of p.R337H was higher in women diagnosed with BC at or before 45 years of age (12.1%) than in those diagnosed at 55 or older (5.1%). An article by Andrade et al [85] suggested that screening for the germline TP53 p.R337H mutation should be recommended for young females with no family history of cancers associated with Li-Fraumeni syndrome. The three authors agree that inheritance of the c.1010G>A variant may significantly contribute to the high incidence of BC in Brazil.…”
Section: Other Bc Susceptibility Mutations In Central and South Amerimentioning
confidence: 99%
“…The fact that none of the carrier parents in this study had cancer at the time of writing of this report suggested that the TP53 R337H mutation was associated with a lower penetrance compared to other germline TP53 mutations. Although initial reports suggested that the main cancer risk associated with the TP53 R337H mutation was the development of childhood ACC, more recent studies reveal that this mutation can be also be identified in patients with CPC, OS, breast cancer and, more recently, neuroblastoma (Giacomazzi et al , ; Seidinger et al , ; Andrade et al , ). All told, it is likely that TP53 R337H predisposes to the more typical cancers seen in LFS, albeit with a lower penetrance.…”
Section: Genotype–phenotype Correlations In Lfsmentioning
confidence: 99%